Serum metabolic changes in rats after intragastric administration of dextromethorphan. (6th September 2016) - Bao, Shihui; Zhang, Jing; Lin, Zixia; Su, Ke; Mo, Jingjing; Hong, Lin; Qian, Shuyi; Chen, Lianguo; Sun, Fa; Wen, Congcong; Wu, Qing; Hu, Lufeng; et al.
Abstract: Dextromethorphan is recognized as a substance of abuse around the world. An estimated 3.1 million people between the ages of 12 and 25 years (5.3%) misused over‐the‐counter cough and cold medications in 2006. In this study, we developed a serum metabolomic method by gas chromatography–mass spectrometry (GC–MS) to evaluate the effect of abuse of dextromethorphan on rats. The dextromethorphan‐treated rats were given 12, 24 and 48 mg/kg (low, medium, high) of dextromethorphan by intragastric administration each day for 3 days. Partial least squares‐discriminate analysis revealed that intragastric administration of dextromethorphan induced metabolic perturbations. Compared with the control (healthy) group, the levels of propanoic acid, urea, heptafluorobutanoic acid, 2‐hexyldecanoic acid and butanedioic acid of the low group decreased; levels of propanoic acid and heptafluorobutanoic acid of the medium group decreased, while that of benzoic acid increased; and levels of 2‐hexyldecanoic acid, glycerol and butanedioic acid of the high group increased. These biomarkers are involved in the citric acid cycle, urea cycle, glycerolipid metabolism and tricarboxylic acid cycle. The results indicate that the metabolomic method by GC–MS may be useful to elucidate abuse of dextromethorphan. According to the pathological changes in the liver at different dosages, dextromethorphan is not hepatotoxic after intragastric administration of 12, 24 and 48 mg/kg for 3 days.